TEACHER AS A ROLE MODEL AND ITS IMPACT ON THE LIFE OF FEMALE STUDENTS - Bashir, Shakila; Bajwa, Munaza; Rana, Sulmaz (International Journal of Research -GRANTHAALAYAH, 2014)
In daily life of students there are many factors that play a vital role in their lives but the major aspect that plays a crucial role in building there personality and in increasing their academic capabilities is a teacher. A teacher is a role model if he/she is attentive towards student’s academic growth and gives equally importance to their personal growth. This study conducted teacher’s social behavior related with student’s personality and teacher’s performance related with student’s academics. Multiple sampling designs including stratified random sampling and cluster random sampling are used; a sample of 300 was selected from students of APWA College, Queen Mary College and Kinnaird College belonging to different socio economic status. A cross sectional study using structured questionnaire was carried out including basic information. Univariate, bivariate and multivariate analyses were carried out on the data collected. The findings demonstrated that out of 300 respondents 212 students take their teachers as a role model. The results of the study showed that there is a need for both teachers and students to become more socially attached with each other by keeping outside classroom relations and better understanding of each other.